The Influence of Characteristics And Patterns of Women Behavior On The Case of Pracancerous Cervical Lesions at Community Health Centers in Pemalang District - Handayani, Saadah; Rini Indriyanti, Dyah (Universitas Negeri Semarang, 2018)
Cervical cancer is a malignant disease that is preceded by the condition of precancerous cervical lesions, namely the existence of cervical intraepithelial dysplasia / neoplasia (NIS). This study attempted to analyze the effect of characteristics and patterns of women behavior on the case of precancerous cervical lesions. The study belonged to observational study with a cross sectional study design. For more, the subjects of the study involved the population of 60 women who were positive for precancerous cervical lesions, while the number of sample was the same as the population, namely 60 respondents sampled by using total sampling technique. Their data were analyzed by using path analysis model. In conclusion, the factors of socioeconomic, age, history of STIs (Sexually Transmitted Infections) directly influence the case of precancerous cervical lesions and indirect effects of parity followed by the use of contraception on the case of precancerous cervical lesions.